2013
DOI: 10.1007/s00128-013-1036-1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Selected Endocrine Disrupting Chemicals in Lake Van, Turkey

Abstract: In the present study, we investigated the distribution of 17β-estradiol (E2), 17α-ethynylestradiol (EE2), alkylphenol ethoxylates (APEs) and organochlorine pesticides (DDE/DDT) in water and sediment samples in the Eastern Anatolia of Turkey, Lake Van, which is the largest soda lake in the world. The procedure consisted of solid phase extraction performed with OASIS HLB cartridges followed by non-competitive enzyme-linked immunosorbent assays (ELISA). The endocrine disrupting compounds E2, EE2, and DDT/DDE were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
4
0
2
Order By: Relevance
“…Among EDCs, the presence of steroid estrogens (such as estrone (E1), 17β-estradiol (E2), estriol (E3), and 17α-ethinylestradiol (EE2)) and phenolic xenoestrogens (such as 4-nonylphenols (4-NP) and bisphenol A (BPA)) deserves particular attention, because the former possesses the highest estrogenicity and the latter has moderate estrogenic potency and widespread applications. Their adverse effects on the reproductive functions of aquatic species and influence on humans have been observed worldwide (Oguz and Kankaya, 2013;Sales et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Among EDCs, the presence of steroid estrogens (such as estrone (E1), 17β-estradiol (E2), estriol (E3), and 17α-ethinylestradiol (EE2)) and phenolic xenoestrogens (such as 4-nonylphenols (4-NP) and bisphenol A (BPA)) deserves particular attention, because the former possesses the highest estrogenicity and the latter has moderate estrogenic potency and widespread applications. Their adverse effects on the reproductive functions of aquatic species and influence on humans have been observed worldwide (Oguz and Kankaya, 2013;Sales et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…A plasticizer (di(2-ethylhexyl) phthalate, 4.37 mg/kg dry) having endocrine-disrupting impacts on fish was determined in the sediment samples of the University shores of Lake Van in 2009 (Unal et al 2014). In an another work, alkylphenol ethoxylates and organochlorine pesticides were identified from Van municipal sewage treatment plant effluent (Oguz and Kankaya 2013). Thus, C. tarichi may be exposed to some natural estrogens or xenoestrogens, which might induce Vtg, possibly derived from the Van municipal sewage treatment plant effluent and other reasons such as agricultural facilities performed in and around Lake Van.…”
Section: Resultsmentioning
confidence: 99%
“…C. tarichi, displaying an anadromous character, migrates to the rivers pouring into the lake for spawning during its reproduction period (April-June) and returns to the lake postspawning. In our other study, endocrine-related disturbances such as altered plasma steroid levels and gonadal abnormalities were determined in C. tarichi (Unal et al 2007), and authors have reported some xenoestrogens such as E 2 , EE 2 , and DDT/DDE in the surface waters and sediments of Lake Van, and sewage effluent discharging into the lake (Oguz and Kankaya 2013). In this study, we aimed to investigate Vtg in the plasma of adult male C. tarichi sampled from Van Edremit Gulf (VEG) of Lake Van as a possible impact of xenoestrogen contamination.…”
mentioning
confidence: 99%
“…Tablo 6. Çeşitli göllerde rastlanan pestisit türleri ve konsantrasyon değerleri Tablo 6 incelendiğinde EPA kirleticiler listesinde yer alan DDT, HCB'lerin atıksu arıtma tesislerinin deşarj nedeniyle içmesuyu kaynağı olan göllerde yüksek konsantrasyonda [40,41] varlığını sürdürdüğü tespit edilmiştir. İçme suyu elde edilen yüzey sularının kalitesinin korunması için belirlenen limit değerlerde HCH (Hekzaklorohekzan)'ın 1 µg/L değerini aşmaması gerekmektedir [43].…”
Section: Göllerde Pestisit Konsantrasyonlarıunclassified